Kajian faktor-faktor fizikal terhadap tahap keselesaan bekerja di Bahagian Casting Shop di kalangan pekerja di Kilang Pembuatan Kereta - Anuar I; Mohamad Jauhari J; Mohd Riduan A. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Background : Level of comfort in working environment can contribute to increase level of health, emotion during working, level of safety, quality and productivity of work. A study of physical factors (heat, noise and lighting) is important to determine the level of comfort during working. This study was carried out to study those physical factors upon comfort level during working among Casting Shop workers in a car manufacturing factory. Methods : Instruments for the physical monitoring including Questemp°36 Thermal Environment Monitor, Sound Level Meter and Lux Meter were used at seven measured areas. The information about the level of comfort during working was collected using questionnaires among 65 respondents by random sampling method. Results : Measured data showed there were four measured areas which Wet Bulb Globe Temperature indoor (WBGTi) value are above the standard limit recommended by ACGIH, three measured areas recorded noise level above the standard limit recommended by Factories and Machineries (Noise Exposure) 1989, while there was no measured area recorded lighting reading below the standard limit recommended by MS ISO 8995:2005. Result from questionnaire found that the majority of the workers did not feel comfortable towards the heat and noise level in their workplace while most of the respondents felt comfortable towards lighting level in their workplace. Mean of WBGTi reading and lighting reading have a significant difference (p<0.05) between half of those measured areas. Mean of noise reading also has a significant difference (p<0.05) between those measured areas. This study also found that there was a relationship between level of health, emotion during working, level of safety, quality and productivity of work and. Conclusion : This study shows that the physical factors influenced the level of comfort during working among Casting Shop workers.